2021
DOI: 10.1186/s13148-021-01079-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metabolic memory on inflammation and fibrosis associated with diabetic kidney disease: an epigenetic perspective

Abstract: Diabetic kidney disease (DKD) is one of the most common microvascular complication of both type 1 (T1DM) and type 2 diabetes mellitus (T2DM), and the leading cause of end-stage renal disease (ESRD) worldwide. Persistent inflammation and subsequent chronic fibrosis are major causes of loss of renal function, which is associated with the progression of DKD to ESRD. In fact, DKD progression is affected by a combination of genetic and environmental factors. Approximately, one-third of diabetic patients progress to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 141 publications
1
47
0
Order By: Relevance
“…The interest in epigenetic modifications in DN has in part been driven by their potential role in the phenomenon of “metabolic memory,” whereby individuals with diabetes and long-term normoglycemia (>25 years) still have an increased risk of DN due to poor glucose control in the past ( 97 ). There is increasing evidence that epigenetic changes are associated with DN ( 98 ). Although the majority of epigenetic studies concern nuclear DNA modifications, mitoepigenetics also has an important role in a variety of diseases, including cardiovascular disease, obesity, and diabetes ( 99 ).…”
Section: Genetics Of Mitochondrial Dysfunction In Dnmentioning
confidence: 99%
“…The interest in epigenetic modifications in DN has in part been driven by their potential role in the phenomenon of “metabolic memory,” whereby individuals with diabetes and long-term normoglycemia (>25 years) still have an increased risk of DN due to poor glucose control in the past ( 97 ). There is increasing evidence that epigenetic changes are associated with DN ( 98 ). Although the majority of epigenetic studies concern nuclear DNA modifications, mitoepigenetics also has an important role in a variety of diseases, including cardiovascular disease, obesity, and diabetes ( 99 ).…”
Section: Genetics Of Mitochondrial Dysfunction In Dnmentioning
confidence: 99%
“…15 Recent studies indicated that DN is a chronic inflammatory immune disorder. 16–18 Crosstalk between cellular metabolic functions and immune activation (immune-metabolism) induces the infiltration of inflammatory cells into the kidneys, contributing to the progression of chronic kidney diseases and the decline in the glomerular filtration rate. 19,20 Structural and functional disorders of renal failure are strongly related to the overproduction of proinflammatory mediators, suggesting that inflammatory responses play crucial roles in the pathophysiology of DN.…”
Section: Introductionmentioning
confidence: 99%
“…Fibro-inflammatory cues are the cardinal molecular signals that drive DN pathogenesis and progression [1,[6][7][8][9]29,30]. Notably, several studies have shown that serum amyloid A (Saa) is a key potential mediator of danger signals that influence inflammatory processes in several chronic inflammatory diseases, such as rheumatoid arthritis, atherosclerosis, obesity, and kidney diseases [17,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%